Can the Expiratory Disproportion Index Distinguish PVFMD from Subglottic Stenosis in Obese Patients?. (September 2021) - Calamari, Kevin; Politano, Stephen; Matrka, Laura
Objectives: Expiratory disproportion index (EDI) is the ratio of forced expiratory volume in 1 second (FEV1) divided by peak expiratory flow rate (PEFR) multiplied by 100. Prominent EDI (>50) values can differentiate subglottic stenosis (SGS) from paradoxical vocal fold movement disorder (PVFMD), but this has not been verified when considering body habitus. We hypothesize that the predictive value of elevated EDI in differentiating SGS from PVFMD will be lower in obese patients than non-obese patients. Methods: Patients ≥ 18 years old with recorded PFT values, BMI, and airway imaging were reviewed retrospectively from 01/2011 to 10/2018. EDI was recorded for 4 cohorts: non-obese/SGS, non-obese/ PVFMD, obese/SGS, and obese/ PVFMD, to determine the mean EDI and the sensitivity/specificity of an elevated EDI. Results: Mean EDI values were 69.32 and 48.38 in the non-obese SGS and PVFMD groups, respectively ( P  < .01). They were 58.89 and 47.67 in the obese SGS and PVFMD groups, respectively ( P  < .05). At a threshold of >50, EDI had a sensitivity of 90.0% and specificity of 51.6% in differentiating between SGS and PVFMD cases in non-obese patients and 51.6% and 63.6% in obese patients. Conclusion: Prior literature has established that EDI can distinguish SGS from PVFMD in the general population. Our results show that the mean EDI values were significantly different in both cohorts, but an elevated EDI was not as sensitive at identifying SGS cases in obese patients. This suggests that the EDI should be used with caution in obese patients and should not be relied upon to rule out SGS. Level of Evidence: 3